On the modeling methods of small-scale piezoelectric wind energy harvesting - Zhao, Liya (2018)
The interdisciplinary research area of small scale energy harvesting has attracted tremendous interests in the past decades, with a goal of ultimately realizing self-powered electronic systems. Among the various available ambient energy sources which can be converted into electricity, wind energy is a most promising and ubiquitous source in both outdoor and indoor environments. Significant research outcomes have been produced on small scale wind energy harvesting in the literature, mostly based on piezoelectric conversion. Especially, modeling methods of wind energy harvesting techniques plays a greatly important role in accurate performance evaluations as well as efficient parameter optimizations. The purpose of this paper is to present a guideline on the modeling methods of small-scale wind energy harvesters. The mechanisms and characteristics of different types of aeroelastic instabilities are presented first, including the vortex-induced vibration, galloping, flutter, wake galloping and turbulence-induced vibration. Next, the modeling methods are reviewed in detail, which are classified into three categories: the mathematical modeling method, the equivalent circuit modeling method, and the computational fluid dynamics (CFD) method. This paper aims to provide useful guidance to researchers from various disciplines when they want to develop and model a multi-way coupled wind piezoelectric energy harvester.